A Pilot Study of Non-invasive Sacral Nerve Stimulation in Treatment of Constipation in Childhood and Adolescence - Besendörfer, Manuel; Kohl, Martin; Schellerer, Vera; Carbon, Roman; Diez, Sonja (Frontiers in Pediatrics, 2020)
Background/Aims. Constipation shows both, a high prevalence and a significant impact yet is often perceived as minor and treatment choices are few. The neuromodulation approach is a valuable option to be considered. This study assesses the use of non-invasive sacral nerve stimulation to reduce constipation in children. Methods. Between February 2013 and May 2015, pediatric patients with chronic constipation were treated with this non-invasive neuromodulation procedure, adapted from classical sacral nerve stimulation. A stimulation device attached to adhesive electrodes on the lower abdomen and back generated an electrical field with a stable frequency of 15 Hz via variable stimulation intensity (1-10 V). The effect of therapy was evaluated in routine check-ups and by specialized questionnaires. Results. The study included evaluation of non-invasive sacral nerve stimulation in 17 patients (9 boys, 8 girls, mean age 6.5 years). They underwent stimulation with 6 to 9 V for a mean of 11 hours per day (range 0.5-24 hours) over a mean of 12.7 weeks. Improvement of constipation was achieved in more than half of the patients (12/17) and sustained in almost half of these patients (5/12). Complications were minor (skin irritation, electrode dislocation). Conclusions. Non-invasive sacral nerve stimulation appears to be effective in achieving improvement in pediatric patients with chronic constipation. As an additional external neuromodulation concept, this stimulation may represent a relevant addition to currently available therapeutic options. Further studies are needed to confirm these results.